When faith is forbidden : 40 days on the frontlines with persecuted Christians - Nettleton, Todd; Voice of the Martyrs (Organization) (Chicago : Moody Publishers, 2021)
"Spend forty days getting to know your persecuted brothers and sisters. With When Faith is Forbidden, you'll journey with the Christians who risk their lives to follow Jesus. Each daily devotional includes inspiration and encouragement through the story of a persecuted believer"--
Includes bibliographical references.
Keywords: Persecution -- Biography; Spiritual journals -- Authorship; Biographies